La méthodologie : n’en faire qu’un discours ou bien reconnaître sa nécessité ? - Hervé Ferrière (Clio@Themis)
Why would a historian of science read the work of the recently deceased legal historian Michael Stolleis ? Because his comparatist, transparent and interdisciplinary approach, and his willingness to highlight concrete examples, are already real sources of inspiration for historians. And, because in our time of the immeasurable challenges (ecological, political, legal…), Stolleis' concern for methodological issues makes him a source of reflection on historiographical rules and the very reasons for historians' activity.